Tourism mobility in time and seasonality in tourism. - Fernández-Morales, Antonio (My University, 2017)
In this paper, tourism mobility is studied as a process that affects the population of a geographical area, like a country or a region, from the point of view of the generated trips in the region. To analyse mobility in time, the approach followed consists of estimating seasonal factors to depict the seasonal distribution of trips along the year and calculating Gini indexes as annual measures of seasonal concentration.
Keywords: Turismo; Seasonality; Tourism